Heaven official's blessing = Tian guan ci fu. 7 - Moxiangtongxiu (Seven Seas Entertainment, 2023)
The Kiln is open, and White No-Face is back to his full power. The past eight hundred years have not blunted his hatred nor his obsession with Xie Lian--he aims to break Xie Lian down to nothing, even if all of humanity and the heavens themselves are collateral damage. This time, however, Xie Lian will not face him alone. Together with Hua Cheng--powerful ghost king, stalwart protector, and devoted love--can Xie Lian finally reveal the face behind the mask and put an end to the nightmare forever?